Concurrent Newborn Hearing and Genetic Screening in a Multi-Ethnic Population in South China - Tang, Xiangrong; Liu, Lihua; Liang, Sulan; Liang, Meie; Liao, Tao; Luo, Shiqiang; Yan, Tizhen; Chen, Jianping (Frontiers in Pediatrics, 2021)
Hearing loss is a common sensory deficit in humans with intricate genomic landscape and mutational signature. Approximately 1–3 out of 1,000 newborns have hearing loss and up to 60% of these cases have a genetic etiology. In this study, we conducted the concurrent newborn hearing and genetic screening in 20 mutations (18 pathogenic variants in GJB2, SLC26A4, and MT-RNR1 and 2 uncertain clinical significance variants in GJB3) for 9,506 normal newborns (4,977 [52.4%] males) from 22 ethnic population in South China. A total of 1,079 (11.4%) newborns failed to pass the initial hearing screening; 160 (1.7%) infants failed to pass the re-screening, and 135 (1.4%) infants presented the diagnostic hearing loss. For the genetic screening, 220 (2.3%) newborns who presented at least one of the screened mutations were more likely to fail the hearing screening and have diagnostic hearing loss than mutation-negative newborns. In comparison to the differences of distribution of mutations, we did not identify any significant difference in the prevalence of screened mutations between Han group (n = 5,265) and Zhuang group (n = 3,464), despite the lack of number of minority ethnic groups. Studies including larger number of minority ethnic populations are needed in the future.